A Problem of Enumeration of Two-color Bracelets with Several Variations (Journal of Informatics and Mathematical Sciences, 2011)
We consider the problem of enumeration of incongruent two-color bracelets of $n$ beads, $k$ of which are black, and study several natural variations of this problem. We also give recursion formulas for enumeration of $t$-color bracelets, $t≥3$.
Keywords: Two-color and multi-color bracelets; Convex $k$-gons; Generalized Fibonacci numbers